How do Stakeholders Perceive the Sustainability and Resilience of EU Farming Systems?. (11th December 2020) - Reidsma, Pytrik; Meuwissen, Miranda; Accatino, Francesco; Appel, Franziska; Bardaji, Isabel; Coopmans, Isabeau; Gavrilescu, Camelia; Heinrich, Florian; Krupin, Vitaliy; Manevska‐Tasevska, Gordana; Peneva, Mariya; Rommel, Jens; et al.
Summary: An increasing variety of stresses and shocks provides challenges and opportunities for EU farming systems. This article presents findings of a participatory assessment on the sustainability and resilience of eleven EU farming systems, to inform the design of adequate and relevant strategies and policies. According to stakeholders that participated in workshops, the main functions of farming systems are related to food production, economic viability and maintenance of natural resources. Performance of farming systems assessed with regard to these and five other functions was perceived to be moderate. Past strategies were often geared towards making the system more profitable, and to a lesser extent towards coupling production with local and natural resources, social self‐organisation, enhancing functional diversity, and facilitating infrastructure for innovation. Overall, the resilience of the studied farming systems was perceived as low to moderate, with robustness and adaptability often dominant over transformability. To allow for transformability, being reasonably profitable and having access to infrastructure for innovation were viewed as essential. To improve sustainability and resilience of EU farming systems, responses to short‐term processes should better consider long‐term processes. Technological innovation is required, but it should be accompanied with structural, social, agro‐ecological and institutional changes. Abstract : La diversité croissante des stress et des chocs crée des défis et des opportunités pour les systèmes agricoles de l'Union européenne. Cet article présente les résultats d'une évaluation participative sur la durabilité et la résilience de onze systèmes agricoles dans l'Union européenne, pour éclairer la conception de stratégies et de politiques adéquates et pertinentes. Selon les parties prenantes qui ont participé aux ateliers, les principales fonctions des systèmes agricoles sont liées à la production alimentaire, la viabilité économique et le maintien des ressources naturelles. La performance des systèmes agricoles évalués par rapport à ces cinq fonctions et à cinq autres a été jugée modérée. Les stratégies passées visaient souvent à augmenter la rentabilité du système et, dans une moindre mesure, à coupler la production avec les ressources locales et naturelles, développer l'auto‐organisation sociale, améliorer la diversité fonctionnelle et faciliter des infrastructures d'innovation. Dans l'ensemble, la résilience des systèmes agricoles étudiés a été perçue comme faible à modérée, la robustesse et l'adaptabilité étant souvent dominantes par rapport à la transformabilité. Une rentabilité raisonnable et un accès à des infrastructures d'innovation ont été considérés comme essentiels au développement de la transformabilité. Pour améliorer la durabilité et la résilience des systèmes agricoles de l'Union européenne, les réponses aux processus de court terme devraient mieux prendre en compte les processus de long terme. L'innovation technologique est nécessaire, mais elle doit s'accompagner de changements structurels, sociaux, agro‐écologiques et institutionnels. Abstract : Zunehmend vielfältige Belastungen und Krisen stellen für die landwirtschaftlichen Systeme in der EU eine Herausforderung und zugleich eine Chance dar. In diesem Artikel werden die Ergebnisse einer partizipativen Bewertung der Nachhaltigkeit und Resilienz von elf landwirtschaftlichen Systemen in der EU vorgestellt. Die Ergebnisse sollen die Entwicklung angemessener und relevanter Strategien und Politikmaßnahmen unterstützen. Laut den Beteiligten, die an den Workshops teilgenommen haben, bestehen die Hauptfunktionen der landwirtschaftlichen Systeme in der Nahrungsmittelproduktion, der Wirtschaftlichkeit und der Erhaltung der natürlichen Ressourcen. Die Leistungen der landwirtschaftlichen Systeme, die im Hinblick auf diese und fünf weitere Funktionen bewertet wurden, wurden nur als mäßig empfunden. In der Vergangenheit waren Strategien oft darauf ausgerichtet, das System rentabler zu machen. Sie waren jedoch weniger darauf ausgerichtet, die landwirtschaftliche Produktion mit lokalen und natürlichen Ressourcen, sozialer Selbstorganisation, der Stärkung der funktionalen Vielfalt und der Erleichterung des Zugangs zu Infrastrukturen für Innovationen zu koppeln. Insgesamt wurde die Resilienz der untersuchten landwirtschaftlichen Systeme als gering bis mäßig eingeschätzt, wobei Stabilität und Anpassungsfähigkeit oft die Transformierbarkeit dominierten. Um Transformierbarkeit zu ermöglichen, wurde es als wesentlich angesehen, hinreichend rentabel zu sein und Zugang zu Infrastrukturen für Innovationen zu haben. Um die Nachhaltigkeit und Resilienz der landwirtschaftlichen Systeme in der EU zu verbessern, sollten bei Reaktionen auf kurzfristige Prozesse langfristige Prozesse besser berücksichtigt werden. Technologische Innovationen sind zwar erforderlich, sollten aber mit strukturellen, sozialen, agrarökologischen und institutionellen Veränderungen einhergehen.